Biogeochemical Activity of Methane-Related Microbial Communities in Bottom Sediments of Cold Seeps of the Laptev Sea - Alexander S. Savvichev; Igor I. Rusanov; Vitaly V. Kadnikov; Alexey V. Beletsky; Elena E. Zakcharova; Olga S. Samylina; Pavel A. Sigalevich; Igor P. Semiletov; Nikolai V. Ravin; Nikolay V. Pimenov (Microorganisms, 2023)
Bottom sediments at methane discharge sites of the Laptev Sea shelf were investigated. The rates of microbial methanogenesis and methane oxidation were measured, and the communities responsible for these processes were analyzed. Methane content in the sediments varied from 0.9 to 37 µmol CH4 dm−3. Methane carbon isotopic composition (δ13C-CH4) varied from −98.9 to −77.6‰, indicating its biogenic origin. The rates of hydrogenotrophic methanogenesis were low (0.4–5.0 nmol dm−3 day−1). Methane oxidation rates varied from 0.4 to 1.2 µmol dm−3 day−1 at the seep stations. Four lineages of anaerobic methanotrophic archaea (ANME) (1, 2a–2b, 2c, and 3) were found in the deeper sediments at the seep stations along with sulfate-reducing Desulfobacteriota. The ANME-2a-2b clade was predominant among ANME. Aerobic ammonium-oxidizing Crenarchaeota (family Nitrosopumilaceae) predominated in the upper sediments along with heterotrophic Actinobacteriota and Bacteroidota, and mehtanotrophs of the classes Alphaproteobacteria (Methyloceanibacter) and Gammaproteobacteria (families Methylophilaceae and Methylomonadaceae). Members of the genera Sulfurovum and Sulfurimonas occurred in the sediments of the seep stations. Mehtanotrophs of the classes Alphaproteobacteria (Methyloceanibacter) and Gammaproteobacteria (families Methylophilaceae and Methylomonadaceae) occurred in the sediments of all stations. The microbial community composition was similar to that of methane seep sediments from geographically remote areas of the global ocean.